Violating the salary cap: exploring performance gains in the National Basketball Association - Pradhan, Sean; Leshchinskii, Dima (Frontiers in Sports and Active Living, 2025)
Salary caps, which act as price ceilings for teams on the cost of players, are commonplace in various North American professional sports leagues. Although some leagues have “hard” caps that teams cannot surpass (e.g., the National Football League), the National Basketball Association (NBA) utilizes a more flexible framework known as a “soft” cap, where the cap can be exceeded by paying a luxury tax, or penalty fee. Thus, teams can choose to optimize player salaries within the cap or strategically exceed it, if the marginal benefits outweigh the cost of the luxury tax. The purpose of the current study is to determine if violating the salary cap in the NBA warrants the financial burden associated with the luxury tax. Salary cap data spanning the 2011–2012 to 2023–2024 NBA seasons were collected from Spotrac, while team performance data were obtained from Basketball-Reference. Using each team's estimated luxury tax bill, we categorized teams into either those that violate the cap (violators) or those that do not (non-violators) based on each season. On-court performance and playoff status (playoff vs. non-playoff team) are compared using a series of mixed-effects models with random effects for team and season controlling for market size, operationalized using the population of the Census-defined metropolitan area, and the roster's average age. We test the hypothesis that paying for more expensive rosters justifies financial fines for violating the salary cap due to the ensuing improvement in team performance.